MENGKAJI ULANG KONSEP KEWARGANEGARAAN, KEBANGSAAN, DAN ETNISITAS - Haryo Ksatrio Utomo, M. IP (Jurnal Communitarian (Prodi Ilmu Politik), 2021)
AbstractThis article discusses the theoretical discourse of political identity. The discussion of the article focuses specifically on citizenship, nationality, and ethnicity. These three things limit this article for two reasons. First, social conflicts are often closely related to claims of "authenticity" of symbols of citizenship, nationality, and ethnicity. These three things are often understood as one unit, even though the three actually have conceptual differences. Then, these claims can lead to sharp social conflicts. Second, an understanding of the three provides a deep understanding of the potential conflicts that occur and the appropriate conflict resolution solutions. A comprehensive understanding of the causes of conflict can also avoid the possibility of incorrect application of conflict resolution. Keywords: Political Identity, Ethnicity, Citizens Abstrak Artikei ini membahas diskursus teoritis identitas politik. Pembahasan artikel tersebut memfokuskan perhatian secara spesifik mengenai kewarganegaraan, kebangsaan, dan etnisitas. Ketiga hal tersebut menjadi pembatas artikel ini dengan dua alasan. Pertama, konflik sosial sebenarnya sering berkaitan erat mengenai klaim "keaslian" dari simbol kewarganegaraan, kebangsaan, dan etnisitas. Ketiga hal tersebut sering dipahami sebagai satu kesatuan, padahal ketiganya sebenarnya memiliki perbedaan konseptual. Kemudian, klaim tersebut dapat menyebabkan konflik sosial yang tajam. Kedua, pemahaman atas ketiga tersebut memberikan pemahaman yang mendalam mengenai potensi konflik yang terjadi dan solusi penanganan konflik yang tepat. Pemahaman yang komprehensif atas penyebab konflik juga bisa menghindari kemungkinan penerapan resolusi konflik yang keliru. Kata Kunci: Identitas Politik, Etnis, Warga Negara